Capillary electrophoresis-mass spectrometry analysis of trehalose-6-phosphate in Arabidopsis thaliana seedlings - Delatte, T. L. (Springer-Verlag, 2011)
Trehalose-6-phosphate (T6P) is an intermediate in the plant metabolic pathway that results in trehalose production. T6P has been shown to inhibit the sucrose nonfermenting-1-related protein kinase 1, which is a major regulator of metabolism. The quantitation of T6P has proven difficult due to the complexity of the plant matrix and the low abundance of T6P in plant tissues. The aim of this work was to develop a quantitation method for T6P present in Arabidopsis tissues, with capillary electrophoresis (CE) coupled to electrospray ionization-mass spectrometry (MS) with a sheath liquid (SL) interface. The CE-MS method was first optimized with respect to T6P signal intensity and separation of isomers by studying the composition of the background electrolyte (BGE) and SL. The use of triethylamine (TEA) in the BGE was favorable, providing separation of T6P from sucrose-6-phosphate and minimizing ionization suppression. Replacing ammonium acetate with TEA enhanced T6P signal intensities more than four times. The optimized method allowed quantification of T6P in plant extracts with good linearity (r (2) > 0.99) within a biologically relevant concentration range. The limit of quantification was 80 nM in Arabidopsis extracts, corresponding to 33 pmol/g plant fresh weight. The CE-MS method was applied to the determination of T6P in seedlings from wild type (WT) Arabidopsis and mutants lacking the trehalase AtTRE1, tre1-1, challenged with trehalose or sorbitol. T6P accumulation in tre1-1 plants grown on sorbitol was about twice the level of T6P found in WT. CE-MS is shown to be a fast and reliable technique to analyze phosphodisaccharides for seedling extracts. The low sample volume requirement of CE and its direct MS coupling makes it an attractive alternative for anion-exchange liquid chromatography–MS.